Dataset: Environmental impacts of low and high order detonations in water - Sharma, Bhumika; Wardrop, Joshua; Persico, Federica; Webb, Sally; Coulon, Frederic; Temple, Tracey (Cranfield University, 2026)
The clearance of dumped munitions often relies on Low Order (LO) and High Order (HO) detonation techniques, both of which pose significant risks to aquatic ecosystems. LO detonation leaves behind substantial explosive residues, whereas HO detonation generates intense shock waves and extensive fragmentation. This study examines the environmental impact of these detonation methods, including partial detonation, under semi-controlled conditions using six 1000-litre IBC tanks. Partial detonation represents an incomplete LO event, leaving exposed explosive material in the water. Experimental results showed that LO detonations left an average of 8.7 mg/L of explosive residue, significantly higher than the 1.2 mg/L observed for HO. Fragmentation analysis revealed that HO produced more than twice the number of fragments compared to LO, increasing the potential for physical damage. By integrating these findings with modelling, we estimated fragment stopping distances and the spatial extent of explosive contamination. These insights inform the development of mitigation zones to minimise both chemical and physical environmental impacts, particularly in the context of World War-era munitions clearance.
Raw data for physical and chemical analysis of TNT pipe bomb
Keywords: Underwater detonation; Explosive residues; Fragmentation; Stopping distance; Mitigation zone